LAE PRESENTS: LINE OF SMILES (CIPEEX, 2022)
IT IS COMMON KNOWLEDGE THAT DENTISTRY IS NOW SEEKING PERFECTIONISM TO ACHIEVE THE STANDARDS IMPOSED BY SOCIETY, A STANDARD THAT POINTS WITH A "PERFECT SMILE" TO THE ONE THAT INVOLVES TOTALLY WHITE TEETH AND IN THEIR CORRECT POSITION IN THE DENTAL ARCH. MANY PEOPLE, WITHOUT FIRST WORRYING ABOUT THEIR HEALTH, SEEK TO FOLLOW THE LABELS OF SOCIETY WITHOUT REALIZING WHAT REALLY MATTERS, WHICH IS PHYSICAL AND PSYCHOLOGICAL WELL-BEING. WITH THE THEME "INCLUSION AND ACCESSIBILITY" OF THE IV CULTURAL EXHIBITION OF THE DENTISTRY COURSE, THE ACADEMIC LEAGUE OF ENDODONTICS (LAE) DECIDED TO PRESENT THE DIVERSITY OF SMILES PRESENT WITHIN THE ACADEMIC LEAGUE OF ENDODONTICS THROUGH A PANEL WITH PHOTOS OF THE SMILES OF THE MEMBERS THE LEAGUE. IN ORDER TO BREAK THE STANDARDS PRE-ESTABLISHED BY THE MEDIA, LAE WANTS TO SHOW BY MEANS OF THE INCLUSION OF SEVERAL SMILES, THAT ESCAPE FROM THIS REALITY, THAT PERFECT SMILE DOES NOT HAVE CORRECT FORM BUT IT IS THE ONE THAT DEMONSTRATES THE HAPPINESS THAT IS IN HIS HEART .&NBSP;KEYWORDS(OU PALAVRAS-CHAVE): SMILES. DIVERSITY. INCLUSION.